Evaluation of the Economic Impact on MSMEs Through the Car Free Day (CFD) Program at Merdeka Square, Medan City: A Case Study of Micro Enterprises in the CFD Environment - Chintya Pradilla Putri; Nurbaiti; Tri Inda Fadhila Rahma (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
The Car Free Day (CFD) program at Merdeka Square in Medan City is one of the government's efforts to create a healthy public environment while encouraging economic growth through empowering Micro, Small, and Medium Enterprises (MSMEs). This study aims to determine whether the CFD program at Merdeka Square really has a significant impact on increasing the income of micro businesses. The study used a qualitative method with a case study approach, involving observation, in-depth interviews, and documentation as data collection techniques. The results of the study showed that the CFD program had a significant impact on increasing the income of MSMEs, with some traders recording a turnover of up to two million rupiah in one activity. However, challenges such as tight competition and limited selling time are still faced by business actors. Better location planning and the elimination of stall rental fees have helped improve trader comfort. Thus, CFD has been proven to be a trigger for local economic growth and supports the sustainability of MSMEs in Medan.